PRAKTIK TEKNIK MENYIMPAN MENGGUNAKAN ALAT PERAGA KANTONG NILAI TEMPAT BILANGAN - Susilawati, Ika (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
This research was conducted following the discovery of low proficiency among second-grade elementary school students in addition using the regrouping technique. The study involved 24 second-grade students and their teacher as data sources. Data collection employed multiple methods: interviews, observation, documentation review, tests, and field notes. Data validity was ensured through source triangulation and time triangulation techniques. This classroom action research was designed in two iterative cycles, with each cycle comprising four standard phases: planning, action implementation, observation, and reflection. Pre-intervention assessment revealed an initial mean student score of 59.38. Following Cycle I implementation, significant improvement occurred with the mean score reaching 75. Progress continued in Cycle II, where the mean score rose substantially to 87.5. Based on comprehensive data analysis, it is concluded that the implementation of visual aids effectively enhances students' conceptual understanding and mathematics learning outcomes. The intervention’s efficacy is empirically confirmed through consistent and significant score improvements across research cycles. These findings indicate that visual/manipulative tools play a crucial role in facilitating comprehension of complex addition concepts among elementary-level learners.